Reliability of cross-country ski specific performance tests and physiological measurements in highly-trained Swiss cross-country skiers - Bucher, E.; Wehrlin, J.; Millet, G. P.; Steiner, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Measurements of performance and physiological characteristics in elite athletes need to be reliable and valid, in order to differentiate between meaningful changes, trends and inherent test variability [1]. However, reliability measures for cross-country ski specific test protocols involving various sub-techniques are currently lacking or remain unreported. This study aimed to investigate the test-retest reliability of a comprehensive cross-country ski specific test battery involving endurance, sprint and neuromuscular testing procedures.